Reconstructing Consumer Behavior Evaluation in Islamic Economics: A Conceptualization of Barakah as the Connecting Link between Utility, Maṣlaḥah, and Falāḥ - Dewi Mutmainnah; Yayah Atmajawati; Farida Idayati (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The concept of utility has traditionally been used in conventional economics to evaluate consumer behavior through the level of satisfaction gained from consumption. However, utility is often considered insufficient to capture the ethical, spiritual, and sustainability dimensions emphasized in Islamic economics. Although the concepts of maṣlaḥah and falāḥ have been widely discussed as normative objectives of consumption, the role of barakah has not been systematically formulated within Islamic consumption theory. This study aims to define barakah, examine its relationship to utility, maṣlaḥah, and falāḥ, and develop a conceptual framework that connects these constructs. Using a library research design with a conceptual approach, the study analyzes the literature on Islamic economics, Qur’anic exegesis, ḥadīth, and related interdisciplinary sources through content and comparative analyses, as well as conceptual synthesis. The findings indicate that barakah is a relational quality arising from the acquisition and use of resources in accordance with Islamic ethical principles, resulting in sustainable material, psychological, and social well-being. Furthermore, utility, maṣlaḥah, barakah, and falāḥ form a hierarchical framework rather than competing concepts. Utility reflects subjective satisfaction, maṣlaḥah serves as the normative criterion, barakah evaluates the quality and sustainability of outcomes, and falāḥ represents the ultimate goal. This framework offers a more comprehensive evaluation of consumer behavior within Islamic economics.